Renewable Energy Deployment for Sustainable Development in the Asia Pacific: A Review - Roslan, Farah (International Journal of Energy Economics and Policy, 2021)
The prominence of energy in output expansion and industrial growth in the Asia-Pacific is globally acknowledged. Nevertheless, the vigorous utilisation of energy leads to energy security concerns and price volatility are thought to have directed to an undesirable effect of energy dependence in the region. An application of renewable energy technologies (RETs) could promote the steady development of the region since diversifying fuel resources is the first step to enhance energy security and reducing energy dependence. This paper highlighted the current trend of the energy sector in the Asia-Pacific and discussed some measures in facilitating the deployment of alternative energy in the region. Therefore this paper can provide new insight for further investigations on the current energy sector and the application of clean energy for strengthening energy security in the Asia-Pacific. Keywords: Energy Security, Renewable energy, Asia-Pacific JEL Classifications: Q2, Q3, Q4 DOI: https://doi.org/10.32479/ijeep.9926